2020
DOI: 10.2478/rtuect-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Merit-Order Effect of Load-Shifting: An Estimate for the Spanish Market

Abstract: AbstractRenewable producers can offer selling bids with very low marginal cost since they are not obliged to include on any cost related to the use of energy from the wind or sun. Accordingly, when the Market Operator integrates a renewable bid in the merit-order generation curve, all the generators based on conventional technologies, with higher marginal cost due to the cost of fuels, are displaced to the right. The right-shifting of the merit-order generation curve leads to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous studies have covered topics from the day-ahead market configuration to intermittency, cost, subsidies, incentives, and penetration of RE into the electricity sector, as well as the merit order effect. 46 These effects have been analyzed in recent research of the Spanish/Iberian market, 47,48 the European Energy Exchange power market in Germany, 49,50 the Australian National Electricity Market, the electricity market of California, 19 and Italian power market. 51…”
Section: Background On Renewables Sources and Day-ahead Electricity M...mentioning
confidence: 99%
“…Previous studies have covered topics from the day-ahead market configuration to intermittency, cost, subsidies, incentives, and penetration of RE into the electricity sector, as well as the merit order effect. 46 These effects have been analyzed in recent research of the Spanish/Iberian market, 47,48 the European Energy Exchange power market in Germany, 49,50 the Australian National Electricity Market, the electricity market of California, 19 and Italian power market. 51…”
Section: Background On Renewables Sources and Day-ahead Electricity M...mentioning
confidence: 99%
“…Intensive research work on the effect of wind energy production on the behaviour of power markets has been carried out by several researchers for more than a decade, and several publications imply that increase of wind energy production and subsequent growth in the proportion of wind energy in the overall energy balance should result in a gradual decline of wholesale power prices [10], [12], [2], [13]. A research carried out in Sweden for the period from the year 2000 to 2016 confirmed that, with the increase of wind energy production by 1 %, the wholesale electricity price decreased by approximately 0.08 %, and over a longer period this value may increase to approximately 0.1 % [14].…”
Section: Introductionmentioning
confidence: 99%